Comparing The Effects of Interactivity and Reputation On Purchase Intention in Tiktok Live Commerce - Pratama, Bagas; Fajarwati, Diana; Hadi, Dwi Putranto (Universitas Muhammadiyah Pontianak, 2026)
This study analyses the effects of interactivity and reputation on purchase intention, with trust and perceived value as mediators among TikTok live commerce users. A quantitative approach with purposive sampling was employed, involving 256 respondents who had shopped via TikTok live commerce. Data were analysed using Partial Least Squares Structural Equation Modelling (PLS-SEM) with SmartPLS 4. The results indicate that interactivity and reputation positively and significantly affect trust, perceived value, and purchase intention. Trust and perceived value also significantly influence purchase intention and mediate the effects of interactivity and reputation. These findings highlight the importance of fostering interactivity, maintaining reputation, and strengthening consumer trust and perceived value.